Comparative cytogenetic analysis in 13 tortoise beetles (Coleoptera: Chrysomelidae: Cassidinae) from Brazil - Lopes, Amália T. [UNESP]; Fernandes, Flávia R.; Schneider, Marielle C. (Biology Centre, AS CR, 2016)
In the present work, we have characterized the chromosomes of 13 Cassidinae beetles, belonging to four tribes, the broad aim being to increase the cytogenetic data and establish the mechanisms involved in chromosome evolution of this subfamily, which appear to be conserved karyotypically, i.e. 2n = 16 + Xyp. The analysis of mitotic and meiotic cells revealed a high diversity of diploid numbers (2n = 18, 2n = 22, 2n = 26, 2n = 32, 2n = 36, 2n = 40, 2n = 42), and the presence of sex chromosome system of the Xyp type in most species, with the exception of two representatives that exhibited Xyr and XY systems. C-banding showed constitutive heterochromatin predominantly localized in the pericentromeric region of the chromosomes, but differences regarding the number of chromosomes with positive C-bands, intensity of the blocks, and presence of additional bands in autosomes and/or sex chromosomes were observed among the species investigated. Our data revealed that the karyotype 2n = 16 + Xyp does not occur in all 13 tribes of the Cassidinae characterized cytogenetically, seeming to be only a shared feature among the species of the Cassidini. Variations in the C-band pattern, mainly in closely related species, suggest that the interspecific karyotype diversification occurred as a result of changes in the quantity and distribution of constitutive heterochromatin. The occurrence of the Xyp sex chromosome system in the tribe Mesomphaliini, which showed the highest diversity of simple and multiple systems among the coleopteran as a whole, reinforces the view that derived systems originated by chromosome rearrangements involving the Xyp ancestral system.
Keywords: C-band; Chromosome; Chrysomelidae; Coleoptera; Constitutive heterochromatin; Karyotype; Meiosis; Sex chromosome system